No Assembly Required: Using BTyper3 to Assess the Congruency of a Proposed Taxonomic Framework for the Bacillus cereus Group With Historical Typing Methods - Carroll, Laura M.; Cheng, Rachel A.; Kovac, Jasna (Frontiers in Microbiology, 2020)
The Bacillus cereus group, also known as B. cereus sensu lato (s.l.), is a species complex comprising numerous closely related lineages, which vary in their ability to cause illness in humans and animals. The classification of B. cereus s.l. isolates into species-level taxonomic units is essential for facilitating communication between and among microbiologists, clinicians, public health officials, and industry professionals, but is not always straightforward. A recently proposed genomospecies-subspecies-biovar taxonomic framework aims to provide a standardized nomenclature for this species complex but relies heavily on whole-genome sequencing (WGS). It thus is unclear whether popular, low-cost typing methods (e.g., single- and multi-locus sequence typing) remain congruent with the proposed taxonomy. Here, we characterize 2,231 B. cereus s.l. genomes using a combination of in silico (i) average-nucleotide identity (ANI)-based genomospecies assignment, (ii) ANI-based subspecies assignment, (iii) seven-gene multi-locus sequence typing (MLST), (iv) single-locus panC group assignment, (v) rpoB allelic typing, and (vi) virulence factor detection. We show that sequence types (STs) assigned using MLST can be used for genomospecies assignment, and we provide a comprehensive list of ST/genomospecies associations. For panC group assignment, we show that an adjusted, eight-group framework is largely, albeit not perfectly, congruent with the proposed eight-genomospecies taxonomy, as panC alone may not distinguish (i) B. luti from Group II B. mosaicus and (ii) B. paramycoides from Group VI B. mycoides. We additionally provide a list of loci that capture the topology of the whole-genome B. cereus s.l. phylogeny that may be used in future sequence typing efforts. For researchers with access to WGS, MLST, and/or panC data, we showcase how our recently released software, BTyper3 (https://github.com/lmc297/BTyper3), can be used to assign B. cereus s.l. isolates to taxonomic units within this proposed framework with little-to-no user intervention or domain-specific knowledge of B. cereus s.l. taxonomy. We additionally outline a novel method for assigning B. cereus s.l. genomes to pseudo-gene flow units within proposed genomospecies. The results presented here highlight the backwards-compatibility and accessibility of the recently proposed genomospecies-subspecies-biovar taxonomic framework and illustrate that WGS is not a necessity for microbiologists who want to use the proposed nomenclature effectively.